The complete mitochondrial genome of Pontederia crassipes: using HiFi reads to investigate genome recombination and gene transfer from chloroplast genome - Hao, Zhigang; Jiang, Xiaoqi; Pan, Lei; Guo, Jingyuan; Chen, Yi; Li, Jianqiang; Liu, Biao; Guo, Anping; Luo, Laixin; Jia, Ruizong (Frontiers in Plant Science, 2024)
Water hyacinth (Pontederia crassipes Mart.) is a monocotyledonous aquatic plant renowned for its rapid growth, extensive proliferation, biological invasiveness, and ecological resilience to variations in pH, nutrients, and temperature. The International Union for Conservation of Nature (IUCN) has listed P. crassipes among the top 100 invasive species. However, comprehensive genomic information, particularly concerning its mitochondrial genome (mitogenome), remains surprisingly limited. In this study, the complete mitogenome of P. crassipes was analyzed using bioinformatics approaches. The mitogenome is 399,263 bp long and contains 38 protein-coding genes (PCGs), 24 tRNA genes, and 3 rRNA genes. Sequence analysis revealed that the complete mitogenome of the species contains 3,289 dispersed repeats, and 765 RNA editing sites in protein-coding genes. The P. crassipes mitogenome possessed un-conserved structures, including extensive sequence transfer between its chloroplasts and mitochondria. Our study on the mitogenome of P. crassipes offers critical insights into its evolutionary patterns and phylogenetic relationships with related taxa. This research enhances our understanding of this invasive species, known for its significant biomass and rapid overgrowth in aquatic environments.